Theoretically Based Factors Affecting Diet Quality of Preschool Children: A Cross-Sectional Study - Qutaibah Oudat; Sarah Couch; Elaine Miller; Rebecca C. Lee; Tamilyn Bakas (Children)
Background/Objectives: Diet quality during early childhood significantly influences long-term health outcomes, including obesity and chronic disease risks. Parental feeding practices, dietary beliefs, and demographic factors have been shown to impact children’s diet quality. This study aimed to determine the extent to which the demographic characteristics and the factors of primary caregivers (dietary beliefs, intention to provide a healthy diet, feeding practices) can explain the variance in the diet quality of preschoolers in the US Methods: This descriptive correlational cross-sectional study was guided by the Theory of Planned Behavior (TPB). A total of 146 primary caregivers of preschool children (aged 3–5) were recruited through convenience and snowball sampling. Data were collected using a self-reported questionnaire and a structured telephone interview. Diet quality was assessed using the Dietary Approaches to Stop Hypertension (DASH) score. Hierarchical multiple regression analyses were conducted to determine the factors associated with preschoolers’ diet quality. Results: The mean DASH score was 40.5 (SD = 10.1), reflecting moderate to low diet quality. The results showed that 16% of the variance in diet quality was significantly explained by race (non-White) and three caregiver feeding practices (food as a reward, restriction food for health, and restriction for weight control). Of these, race (non-White) and restriction food for health were significant predictors and associated with lower diet quality in preschoolers. Conclusions: These findings align with previous studies and suggest that the conceptual framework of this study might be further refined and tested in future studies.